Development of automatic meniscus adjustment instrument - Variyart, Weerachai; Wattanahuttakum, Acharawan (Bulletin of Applied Sciences, 2022)
This research is aimed to develop an automatic meniscus adjustment instrument. Its structure and computer software for system controlling are designed and constructed. This designed instrument is equipped with three main parts. Firstly, a pipet holder set is designed for holding the pipette with nominal capacities in the range of 1 ml to 100 ml. The speed and the movement in up-down direction are controlled by motor. Secondly, the set of the liquid suction and release system is the part controlled by the water pump connected to the computer programme and linked to the digital image processing system in real time. Thirdly, the microscope holder set is for holding the digital microscope device, which can move in x y and z axis directions. Our computer software, named as DSS Pipette calibration, is also specially developed to control the entire system of the automatic meniscus adjustment instrument. It efficiently works for operating activities such as the motorized adjustment of the pipette position, the pump controller for suction and release system, the presence of the real-time image processing on the computer screen to view the meniscus, and the meniscus adjustment at the graduation line. The performance of the automatic meniscus adjustment instrument can be examined by the actual volume determination of pipettes. The results obtained from using the developed device show the better measurement accuracy and precision when compared with the result obtained from using the conventional method. This tool also plays an important role in reducing the human error from meniscus setting at the graduation line.